Bronchioloalveolar lung tumors induced in "mice only" by non-genotoxic chemicals are not useful for quantitative assessment of pulmonary adenocarcinoma risk in humans. (6th December 2018) - Smith, Carr J; Perfetti, Thomas A; King, Judy A
Chemicals classified as known human carcinogens by International Agency for Research on Cancer (IARC) show a low level of concordance between rodents and humans for induction of pulmonary carcinoma. Rats and mice exposed via inhalation for 2 years show a low level of concordance in both tumor development and organ site location. In 2-year inhalation studies using rats and mice, when pulmonary tumors are seen in only male or female mice or both, but not in either sex of rat, there is a high probability that the murine pulmonary tumor has been produced via Clara cell or club cell (CC) metabolism of the inhaled chemical to a cytotoxic metabolite. Cytotoxicity-induced mitogenesis increases mutagenesis via amplification of the background mutation rate. If the chemical being tested is also negative in the Ames Salmonella mutagenicity assay, and only mouse pulmonary tumors are induced, the probability that this pulmonary tumor is not relevant to human lung cancer risk goes even higher. Mice have a larger percentage of CCs in their distal airways than rats, and a much larger percentage than in humans. The CCs of mice have a much higher concentration of metabolic enzymes capable of metabolizing xenobiotics than CCs in either rats or humans. A principal threat to validity of extrapolating from the murine model lies in the unique capacity of murine CCs to metabolize a significant spectrum of xenobiotics which in turn produces toxicants not seen in rat or human pulmonary pathophysiology.